Strategické plánování distribučních cest pro produkty chemických oborů podnikání - Branská, Lenka; Lošťáková, Hana (Univerzita Pardubice, 2001)
Marketing managers of many industrial companies more and more accent an importance of distribution for obtaining and keeping customers. Systematic methodology for distribution channels strategic planning of business areas intended for production consumption does not exist so far. This article describes distribution channels strategic planning methodology and primary research results targeted to verification applicability of this methodology in industrial practice.
Keywords: chemický průmysl; strategické plánování; distribuce